Saline-alkali soil geopolymer cement, saline-alkali soil slurry, solidified soil and preparation method and application of saline-alkali soil geopolymer cement and saline-alkali soil slurry

By using single-component saline-alkali earth base polymer cement in saline-alkali earth, and using the double alkali excitation mechanism of crystalline and amorphous silicon-aluminum, the strength of geopolymer cement in the prior art is solved. The strength of geopolymer cement in the prior art is insufficient when curing saline-alkali earth is performed. and complex process problems, high-strength curing and simplifying process effects are achieved.

CN119409432APending Publication Date: 2025-02-11樊鲁倩
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411554838.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing poly cement has shortcomings in strength and application, especially when curing saline-alkali soil, which has low strength and complex processing technology.

Method used

A single-component saline-alkali earth base polymer cement is used, and its raw materials include crystalline and amorphous silicon-aluminum raw materials. The silicon-aluminum is activated through a two-stack alkali excitation mechanism to form a high-strength cured body.

Benefits of technology

The efficient curing of saline-alkali soil is achieved, ensuring the structural strength and performance of the cured body, and simplifying the construction process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409432A_ABST
    Figure CN119409432A_ABST
Patent Text Reader

Abstract

The invention discloses saline-alkali soil geopolymer cement, saline-alkali soil slurry, solidified soil and a preparation method and application thereof, and belongs to the technical field of soil solidification materials. The single-component saline-alkali soil-based geopolymer cement is prepared from the following raw materials in percentage by mass: 35-50% of a crystalline-state silicon-aluminum raw material and 20-30% of an amorphous-state silicon-aluminum raw material, the content of silicon-aluminum oxide in the crystalline silicon-aluminum raw material is not less than 65% of the total amount of the crystalline silicon-aluminum raw material. The saline-alkali soil-based geopolymer cement is used as a raw material for curing the saline-alkali soil, so that on one hand, the technical problem that all crystalline-state silicon-aluminum is generally required to be subjected to high-temperature calcination and activation treatment to form amorphous-state silicon-aluminum and then can be used for geopolymer cement in the prior art can be effectively solved; the cost of raw materials for producing the geopolymer cement is greatly reduced; on the other hand, the solidification effect on the saline-alkali soil can be effectively guaranteed, and the manufacturing process and the construction process are easy to operate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soil solidification materials, and in particular relates to a saline-alkali soil-based polymer cement, a saline-alkali soil slurry, solidified soil, and a preparation method and application thereof. Background Art

[0002] With the rapid development of economy and the rapid advancement of science and technology, mineral resources and energy materials are becoming increasingly depleted, and energy conservation, emission reduction and green environmental protection have attracted much attention. The preparation of traditional inorganic non-metallic materials usually requires high-temperature sintering above 1000℃, which consumes energy and produces a large amount of greenhouse gases and toxic gases. Compared with traditional silicate cement, geopolymer cement does not require high-temperature calcination during the preparation process, and its carbon dioxide emissions are 70% to 80% lower than those of silicate cement production. Moreover, its raw materials are mostly aluminum, silicate minerals or industrial by-products such as fly ash and slag that are activated by calcination at temperatures below 1000℃, which has obvious economic and environmental benefits.

[0003] There are many application examples of geopolymer cement using metakaolin as raw material. Metakaolin polymer cement material has many excellent properties that are difficult to achieve with cement concrete, good mechanical properties, abundant raw materials, simple process, low price, energy saving and environmental protection. Compared with ordinary cement materials, metakaolin polymer cement materials also have good corrosion resistance and durability. Generally, cement-based materials will have obvious structural damage and disintegration after 15 years of service, while the structure of geopolymers is still intact after hundreds of years. Therefore, geopolymers can be widely used in building materials, transportation, metallurgy, nuclear waste treatment and emergency repair engineering. However, up to now, the research on geopolymers has focused on various alkali activators and siliceous aluminum industrial solid wastes as raw materials for geopolymers, and the geopolymer cement concrete materials prepared therefrom. There are fewer studies on geopolymers for solidifying soil, and geopolymers are mostly multi-component before use, which is extremely inconvenient to use.

[0004] After searching, the application case with application number 201810045798.X discloses a single-component alkali-activated cementitious material with lime-sodium carbonate as the activator, which is prepared by dry mixing a composite component prepared by lime and sodium carbonate in a molar ratio of 1:1 as the activator, and a volcanic ash active material as the object to be activated. The compressive strength of the cementitious material is 1.2 to 1.3 times that of P.O42.5 cement, and it can be used directly by adding water. The alkalinity is low in the initial mixing stage, the setting time is moderate, and it can be adjusted by adjusting the alkali dosage or the ratio of raw / slaked lime, and has good engineering application prospects. However, the limitation of this patent is that it only studies the effect of the activator ratio on the performance of cement soil, and the performance of the obtained cement soil still needs to be further improved, and it is only suitable for solidifying ordinary clay.

[0005] The application number 202210439790.8 discloses a composite foundation for single-component geopolymer reinforced soil and its construction method, including: obtaining raw materials and adjusting their silicon-aluminum ratio, adding solid alkali activator after sintering and grinding to obtain single-component geopolymer cement, and adding water to the single-component geopolymer cement to obtain slurry, and then using wet spraying to mix the slurry and the reinforced soil to obtain a single-component geopolymer cement mixing pile. The amount of powdered caustic soda in the activator of this application accounts for 8-12% of the mass percentage of the silicon-aluminum raw materials, and the amount of powdered sodium metasilicate accounts for 10-15% of the mass percentage of the silicon-aluminum raw materials, that is, the amount of the activator is too high, and during the construction of the mixing pile, the amount of single-component geopolymer also accounts for more than 25% of the solidified soil, and only low-strength solidified soil piles can be obtained.

[0006] Application No. 201911159539.0 discloses a method for preparing geopolymer cement using three solid wastes, namely fly ash, bottom slag and hydrocarbide slag, as the main raw materials, which can significantly reduce material costs and improve geopolymer durability. However, the activator of the geopolymer cement is still liquid, and it is a two-component product when used. The preparation steps are relatively large, which is extremely inconvenient when used in soil solidification and concrete preparation.

[0007] The application with application number 202110612172.4 discloses a single-component geopolymer curing agent based on multi-solid waste and a preparation method thereof. The curing agent is mixed with water to cause the exciting component to undergo a geopolymerization reaction with the curing material component and the reinforcing component to generate geopolymer gel and CSH gel, which tightly cement the soil particles together to form a stable solidified body. The reinforcing component in the geopolymer is at least one of fly ash, blast furnace slag, and metakaolin; the exciting component is at least one of instant powdered sodium silicate, sodium metasilicate pentahydrate, anhydrous sodium carbonate, and analytically pure solid sodium hydroxide; in addition, ordinary Portland cement is used as a regulating component. However, when the geopolymer-cured soil in this application is used as a roadbed, it cannot exhibit the high strength and early strength properties of the geopolymer. In addition, in some remote areas, various industrial solid wastes are in short supply. The solidification materials needed for soil solidification, especially saline-alkali soil solidification, will not only lead to high raw material transportation costs, but also low-cost activators are mostly liquids, and it is difficult to process single-component geopolymer cement. At the same time, there are many processing links when used for saline-alkali soil solidification construction, which is not convenient for large-scale construction applications. Summary of the invention

[0008] 1. Technical issues to be solved

[0009] One of the purposes of the present invention is to provide a single-component saline-alkali soil-based polymer cement and a preparation method thereof, so as to solve the technical problems that the existing geopolymer cement has low strength and can usually only be used to solidify ordinary clay; or its processing technology is relatively complicated and inconvenient to use;

[0010] The second object of the present invention is to provide a single-component curable saline-alkali soil slurry and its preparation process. The curable soil slurry uses saline-alkali soil as the object to be cured and saline-alkali soil-based polymer cement as the curing cementitious material. It can not only effectively realize the curing treatment of saline-alkali soil, but also ensure the structural strength and other performance of the obtained cured soil, and its overall construction process is simple to operate.

[0011] Furthermore, the present invention also provides a saline-alkali solidified soil;

[0012] At the same time, the present invention also provides an application of the saline-alkali soil-based polymer cement, the solidifiable saline-alkali soil slurry or the saline-alkali solidified soil in ditch slopes or road subgrades.

[0013] 2. Technical solution

[0014] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0015] The first aspect of the present invention provides a single-component saline-alkali soil-based polymer cement, whose raw materials include crystalline siliceous-aluminous raw materials and amorphous siliceous-aluminous raw materials, wherein the mass of the crystalline siliceous-aluminous raw materials accounts for 35% to 50% of the total amount of crystalline and amorphous siliceous-aluminous raw materials, and the content of silicon aluminum oxide in the crystalline siliceous-aluminous raw materials is not less than 65% of the total amount of the crystalline siliceous-aluminous raw materials.

[0016] At present, the existing geopolymer cement is usually formed by polymerization reaction of siliceous aluminum precursor materials (siliceous aluminum is in an amorphous phase) obtained by high-temperature calcination activation or high-temperature melting and rapid cooling of metakaolin, fly ash, slag, etc. as the activating component under the action of alkaline activators. On the one hand, the mechanical strength of the geopolymer cement is relatively low, and it cannot be effectively applied to the solidification treatment of saline-alkali soil; on the other hand, the operation process when it is applied to soil solidification is also relatively complicated. Based on the above situation, the present invention uses crystalline siliceous aluminum and amorphous siliceous aluminum raw materials together as the activatable components of saline-alkali soil-based polymer cement, thereby effectively solving the above technical problems.

[0017] Specifically, those skilled in the art generally believe that crystalline silica-alumina must be subjected to high-temperature calcination treatment to make it amorphous silica-alumina before it can be effectively used in the solidification treatment of soil. However, the inventors of this application unexpectedly discovered in experimental research that crystalline silica-alumina can be used without high-temperature activation. It should also be noted that the amount of crystalline silica-alumina raw material added and the content of silica-alumina in the crystalline silica-alumina raw material in this application are more critical. Only by compounding crystalline silica-alumina and amorphous silica-alumina and strictly controlling their mass ratio and the content of silica-alumina in the crystalline silica-alumina raw material can the hardening strength of geopolymer cement be effectively guaranteed to meet the needs of engineering applications.

[0018] In addition, all numerical ranges in the present application include any specific value within the range and any numerical range within the range.

[0019] According to the saline-alkali soil-based polymer cement of any embodiment of the first aspect of the present invention, the compressive strength of the hardened body of the saline-alkali soil-based polymer cement at a water-cement ratio of 0.5 is 15-25 MPa at 3d, 25-35 MPa at 7d, 35-95 MPa at 28d, and the softening coefficient is ≥0.9.

[0020] According to the saline-alkali soil-based polymer cement of any embodiment of the first aspect of the present invention, the crystalline siliceous-aluminous raw material is well-crystalline saline-alkali soil; and / or the amorphous siliceous-aluminous raw material is siliceous-aluminous industrial solid waste, and the mass ratio of saline-alkali soil to siliceous-aluminous industrial solid waste is (35-50): (50-65). By using saline-alkali soil as the source of crystalline siliceous-aluminous raw material, the comprehensive utilization of saline-alkali soil can be effectively achieved.

[0021] Furthermore, the salt-alkali content in the saline-alkali soil converted into alkali metal oxides is not less than 5%.

[0022] Furthermore, the saline-alkali soil is silty saline-alkali soil or clayey saline-alkali soil, preferably silty saline-alkali soil, and the particle size of the saline-alkali soil is less than 200 meshes. More preferably, the content of silicon aluminum oxide in the saline-alkali soil is not less than 69%.

[0023] Furthermore, the silicon-aluminum industrial solid waste is one of slag powder, straw ash, silica ash or any combination thereof.

[0024] Further preferably, the slag powder is made by grinding water-quenched blast furnace slag, and its specific surface area is greater than 400m 2 / kg, product grade ≥S95.

[0025] Further preferably, the SiO in the silica ash 2 The content is ≥95%, and the mass proportion of silica fume (relative to the total mass of saline-alkali soil and silica-alumina industrial solid waste) does not exceed 5%.

[0026] Further preferably, the straw ash is straw burning ash from a biomass power plant, with a residual carbon content of ≤5% and a moisture content of less than 1%. When straw ash is used as siliceous and aluminous industrial solid waste, the potassium oxide, silicon oxide, and aluminum oxide in the straw ash have a low temperature during the combustion process, and there is no glass phase produced by the melting phase. The particles have a small particle size and a large specific surface area, and are easily dissolved in alkaline liquids to disintegrate and undergo a geopolymer network reconstruction reaction, thereby accelerating the speed of obtaining geopolymer cement stone products.

[0027] According to any embodiment of the first aspect of the present invention, the saline-alkali soil-based polymer cement, the raw materials of the geopolymer cement further include an additional alkaline activator, the mass of the additional alkaline activator (converted into Na 2 O or K 2 O) is 3% to 6% of the total amount of saline-alkali soil and silicon-alumina industrial solid waste.

[0028] The saline-alkali soil and silico-alumina industrial solid waste both contain alkaline components and silico-alumina components. The saline-alkali soil is activated by alkali for a long time, its surface is activated, and the lattice is also activated. It contains a certain amount of saline-alkali components. When it is mixed with silico-alumina industrial solid waste for processing geopolymer cement, the saline-alkali components in the saline-alkali soil can perform a first reactivation on the saline-alkali soil, and then perform a second reactivation treatment (i.e., double alkali excitation) by adding external alkali, which can not only effectively ensure the activation effect of the active components, but also effectively reduce the use of external alkaline activators, thereby ensuring the strength of the resulting geopolymer cement.

[0029] Furthermore, the added alkaline activator comprises at least two of alkali metal hydroxides, silicates, sulfates and carbonates, preferably a combination of sodium silicate and at least one of alkali metal hydroxides, sulfates and carbonates, and more preferably a combination of sodium hydroxide and sodium silicate, a combination of sodium hydroxide, sodium silicate and sodium carbonate, or a combination of sodium hydroxide, sodium silicate, sodium carbonate and sodium sulfate.

[0030] Preferably, the mass of sodium silicate accounts for 50% to 80% of the total amount of the added alkaline activator, and more preferably 60 to 70%, and the modulus range of sodium silicate is preferably 1 to 2.

[0031] The second aspect of the present invention also provides a method for preparing saline-alkali soil-based polymer cement as described in the first aspect, comprising: a step of uniformly mixing raw materials comprising crystalline siliceous-aluminous raw materials, amorphous siliceous-aluminous raw materials and an external alkaline activator.

[0032] It should be noted that the raw materials including the crystalline silicon-aluminum raw material, the amorphous silicon-aluminum raw material and the external alkaline activator are mixed uniformly, and there is no special restriction on the mixing and adding order of the three raw materials.

[0033] As one implementation method, the added alkaline activator is a liquid raw material, and the raw materials including crystalline silicon-alumina, amorphous silicon-alumina and the added alkaline activator are mixed evenly, preferably including:

[0034] 1) Weighing crystalline silicon-alumina raw materials and alkaline activators according to the mixing ratio, drying and ball milling to form super-alkaline saline-alkali soil powder, wherein the moisture content of the super-alkaline saline-alkali soil powder is less than 1%; wherein the drying temperature is less than 300° C.;

[0035] 2) Super alkaline saline-alkali soil powder and amorphous siliceous-aluminous raw materials are weighed according to the mix ratio, and the saline-alkali soil-based polymer cement is obtained by vigorously stirring and mixing them evenly.

[0036] Furthermore, the stirring speed of the strong stirring is ≥45 rpm, and the stirring time is not less than 5 minutes.

[0037] As another implementation method, the additional alkaline activator is a powder raw material, and the raw materials including crystalline silica-alumina, amorphous silica-alumina and the external alkaline activator are mixed evenly, preferably including: weighing the dried crystalline silica-alumina raw material, amorphous silica-alumina raw material and powdered alkaline activator according to the mixing ratio, and directly mixing them evenly by strong stirring to obtain saline-alkali soil-based polymer cement.

[0038] Furthermore, the stirring speed of the strong stirring is ≥45 rpm, and the stirring time is not less than 5 minutes.

[0039] According to the preparation method of any embodiment of the second aspect of the present invention, the prepared saline-alkali soil-based polymer cement has a compressive strength of 15-25 MPa at a water-cement ratio of 0.5, 25-35 MPa at 7d, 35-95 MPa at 28d, and a softening coefficient ≥0.9.

[0040] The third aspect of the present invention also provides a curable saline-alkali soil slurry, the raw materials of which include original saline-alkali soil, and saline-alkali soil-based polymer cement according to any embodiment of the first aspect of the present invention or saline-alkali soil-based polymer cement prepared by the preparation method according to any embodiment of the second aspect of the present invention. By adopting the saline-alkali soil-based polymer cement of the present invention, saline-alkali soil can be effectively cured and the strength of the obtained cured soil can be guaranteed, and the overall construction process is simple to operate and is easy to promote and apply.

[0041] According to the curable saline-alkali soil slurry of any embodiment of the third aspect of the present invention, the mass ratio of the saline-alkali soil-based polymer cement to the original saline-alkali soil can be selected to be 1:1.5-1:9, 1:2-1:10 or 1:8-1:12 according to different specific application scenarios.

[0042] According to the solidifiable saline-alkali soil slurry of any embodiment of the third aspect of the present invention, the water-cement ratio of the solidifiable saline-alkali soil slurry is 0.35-1.0, preferably 0.35-0.6.

[0043] According to the curable saline-alkali soil slurry of any embodiment of the third aspect of the present invention, the slurry is injected into a mortar test mold of 70.7mm×70.7mm×70.7mm and vibration-formed. Then, under the curing conditions of 20°C and 90% relative humidity, the unconfined compressive strength at the ages of 3 days, 7 days and 28 days is 0.5-4MPa, 1.5-7MPa and 3-12MPa respectively, and the softening coefficient is ≥0.85. After 25 freeze-thaw cycles from room temperature to -20°C, the strength and mass losses are negligible.

[0044] According to the curable saline-alkali soil slurry of any embodiment of the third aspect of the present invention, the unconfined compressive strength of the slurry after curing and water retention for 7 days is 1-5 MPa, and the softening coefficient is ≥0.85, which can meet the construction requirements of road subgrade and ditch slope.

[0045] The fourth aspect of the present invention further provides a method for preparing a solidifiable saline-alkali soil slurry as described in any embodiment of the third aspect of the present invention, comprising:

[0046] The original saline-alkali soil is mixed with the saline-alkali soil-based polymer cement, and water is added to reach a desired water-cement ratio.

[0047] The fifth aspect of the present invention also provides a saline-alkali solidified soil, the raw materials of which include the saline-alkali soil-based polymer cement described in any embodiment of the first aspect of the present invention, or prepared by the preparation method of any embodiment of the second aspect of the present invention, or the saline-alkali solidified soil is formed by solidifying a curable saline-alkali soil slurry prepared by any embodiment of the third aspect of the present invention, or prepared by the preparation method of any embodiment of the fourth aspect of the present invention.

[0048] The sixth aspect of the present invention also provides a saline-alkali soil-based polymer cement as described in any embodiment of the first aspect of the present invention, or prepared by the preparation method of any embodiment of the second aspect of the present invention, or a solidifiable saline-alkali soil slurry as described in any embodiment of the third aspect of the present invention, or prepared by the preparation method of any embodiment of the fourth aspect of the present invention, or a saline-alkali solidified soil as described in any embodiment of the fifth aspect of the present invention, in soil solidification, ditch slope or road subgrade.

[0049] Furthermore, when applied to ditch slope construction, the saline-alkali soil-based polymer cement is added to the original saline-alkali soil at the bottom of the drainage ditch in a ratio of cement: soil = 1:1.5 to 1:10, and saline-alkali water is supplemented to the required water-cement ratio, and vigorously stirred to obtain a solidifiable saline-alkali soil slurry. The slurry is injected into the slope casting area surrounded by the formwork support for the drainage ditch slope protection construction, and vibrated to form. After hardening, the formwork is removed, and the plastic film is covered for water conservation maintenance. After curing for 7 days, the core is taken, and the core sample is intact. The 7d unconfined compressive strength of the core sample is 1 to 5MPa (7d), and the softening coefficient is ≥0.85. After the freeze-thaw process in winter and spring, the slope is intact, and the strength does not decrease under strong sunlight.

[0050] Furthermore, when applied to road subgrade construction, the saline-alkali soil-based polymer cement is added to the original saline-alkali soil in a ratio of geopolymer cement: soil = 1:8 to 1:12, and saline-alkali water is sprayed to supplement the soil to a moisture content required for the maximum compaction degree. After being fully mixed, the soil is rolled to form a road subgrade, and the compaction degree of the subgrade-solidified saline-alkali soil is ≥90%.

[0051] After construction, the road is covered with plastic film for water-retaining maintenance. The core is taken after 7 days of maintenance. The core sample is complete, and the unconfined compressive strength of the core sample is 1 to 5 MPa (7d), and the softening coefficient is ≥0.85. After the freeze-thaw process in winter and spring, the roadbed is intact without slurrying. The strength does not decrease under strong sunlight.

[0052] 3. Beneficial effects

[0053] In summary, the technical solution provided by the present invention can achieve the following beneficial effects compared with the prior art:

[0054] (1) The raw materials of the saline-alkali soil-based geopolymer cement of the present invention contain some crystalline siliceous-aluminous raw materials. By using them together with amorphous siliceous-aluminous raw materials as activatable components of geopolymer cement, on the one hand, it can effectively solve the technical problem in the prior art that all crystalline siliceous-aluminous raw materials usually need to be subjected to high-temperature calcination activation treatment, that is, converted into amorphous siliceous-aluminous components before they can be used in geopolymer cement. The high-temperature calcination activation process of kaolin and clay as the siliceous-aluminous raw materials of geopolymer cement is omitted, thereby greatly reducing the raw material cost of geopolymer cement production. On the other hand, the geopolymer cement can be effectively used for the solidification treatment of saline-alkali soil and can effectively ensure the structural strength of the solidified body. At the same time, the production process of the geopolymer cement is simple to operate, which is convenient for promotion and application.

[0055] (2) The crystalline silica-alumina raw material of the present invention directly adopts original saline-alkali soil. The original saline-alkali soil has been soaked in saline-alkali water for a long time and contains silica-alumina and saline-alkali components. The silica-alumina component serves as the main activating component of geopolymer cement, and the saline-alkali component can serve as a partial activating component. This can effectively reduce the amount of added alkaline activator and prevent the influence of excessive addition on the strength of geopolymer cement; at the same time, the surface alkali precipitation phenomenon of geopolymer cement after hydration can be controlled.

[0056] (3) When the geopolymer cement of the present invention is used, the alkaline activator first activates the difficult-to-react saline-alkali soil, and then activates the easily reactive amorphous siliceous-aluminous components with volcanic ash reaction ability, thereby effectively alleviating the rapid reaction of the geopolymer, and thus fully guaranteeing and effectively controlling the construction process.

[0057] (4) When producing the geopolymer cement of the present invention, either liquid activator raw materials or powder activator raw materials can be used, and the overall production process is simple to operate, especially convenient for solidification treatment of saline-alkali soil in remote areas, and the processing cost is relatively low.

[0058] (5) The geopolymer cement of the present invention uses original saline-alkali soil as the main source of siliceous and aluminous components. When it is used to solidify saline-alkali soil, after the geopolymer reaction is completed, the alkali ions therein will be transported and migrated to the adjacent saline-alkali soil, thereby increasing the alkali ion concentration in the solidified saline-alkali soil and allowing the secondary geopolymer reaction in these solidified bodies to continue to occur, thereby making the solidified body structure dense, with improved later strength, improved freeze-thaw resistance, drought resistance and weather resistance, and extended service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 This is the thermogravimetric-differential thermal analysis curve of the original saline-alkali soil in Bachu.

[0060] Figure 2 This is the XRD pattern of the original saline-alkali soil in Bachu.

[0061] Figure 3 It is a schematic diagram of the structure when geopolymer cement is applied to ditch slope in an embodiment of the present invention.

[0062] Attached Figure 3 In: 1. Alkali drainage channel; 2. Saline-alkali water; 3. Saline-alkali water discharge channel; 4. Solidified soil slope; 5. Saline-alkali soil. DETAILED DESCRIPTION

[0063] In order to further understand the content of the present invention, the present invention is now described in detail in conjunction with specific embodiments. The activator raw materials used in Examples 1 to 5 are liquid raw materials, and the activator raw materials used in Examples 6 and 7 are powder raw materials. It should also be noted that the source of saline-alkali soil in this application is not limited, as long as the content requirement of silicon aluminum oxide in the saline-alkali soil (not less than 65%) is met. The following embodiments only use the silty saline-alkali soil of a drainage ditch in Bachu County, southern Xinjiang as an example.

[0064] Example 1

[0065] This embodiment provides a single-component geopolymer cement with saline-alkali soil as the main raw material, wherein the raw materials are composed of saline-alkali soil, slag powder and alkaline activator, wherein the mass proportion of saline-alkali soil and slag powder is 50% respectively, and the alkaline activator (equivalent to Na 2 The mass of the raw material is 6% of the sum of the mass of saline-alkali soil and slag powder.

[0066] Specifically, the saline-alkali soil used in this embodiment is silty saline-alkali soil from a drainage ditch in Bachu County, southern Xinjiang. The particle size of the saline-alkali soil is less than 200 mesh. Table 1 below shows the XRF chemical composition analysis results of the saline-alkali soil.

[0067] Table 1 XRF chemical composition analysis results of saline-alkali soil used in this example

[0068] Chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> CaO <![CDATA[Fe 2 THE 3 ]]> MgO <![CDATA[K 2 The]]> <![CDATA[Na 2 The]]> other content(%) 52.99 16.08 13.70 5.87 3.78 3.41 1.84 2.33

[0069] Combination Figure 1 It can be seen that the salinity and alkali content of the saline-alkali soil used in this embodiment is converted into alkali metal oxide K 2 O+Na 2 O accounts for 5.25% of the mass in saline-alkali soil. Figure 1 The thermogravimetric-differential thermal analysis curve of the saline-alkali soil shows that the saline-alkali components in the saline-alkali soil are mainly carbonates of alkali metals. Figure 2 The XRD spectrum of the saline-alkali soil shows that the diffraction peak intensity of the crystals in the saline-alkali soil is relatively high, which means that the crystals of each phase are intact. The main crystal phases in the saline-alkali soil are silica-alumina (silicon-alumina), calcium feldspar, albite and potassium feldspar, and calcite (CaCO 3 ) crystals; the slag powder is made by grinding water-quenched blast furnace slag, has an amorphous structure, and has a specific surface area of ​​410m 2 / kg, the product grade is S95; the alkaline activator is composed of sodium hydroxide and sodium silicate, the sodium silicate accounts for 65% of the alkaline activator, and the sodium silicate modulus is 1.

[0070] The preparation process of the single-component saline-alkali soil-based polymer cement of this embodiment includes:

[0071] 1) weighing saline-alkali soil and alkaline activator according to the mixing ratio, drying and ball milling to form super alkaline soil powder, the drying temperature is 250° C., and the moisture content of the super alkaline soil powder is 0.5%;

[0072] 2) According to the mix ratio, super alkaline soil powder and slag powder are weighed and vigorously stirred in a high-power mixer at a speed of 45 rpm for not less than 5 minutes. In this embodiment, the mixture is stirred for 10 minutes to obtain a saline-alkali soil-based polymer cement. The unconfined compressive strength of the net slurry hardened body of the saline-alkali soil polymer cement at a water-cement ratio of 0.5 is 15 MPa at 3d, 25 MPa at 7d, 90 MPa at 28d, and the softening coefficient is 0.95.

[0073] The saline-alkali soil-based polymer cement obtained in this embodiment is applied to the construction of road subgrade. On the compacted saline-alkali soil roadbed, the first layer of saline-alkali soil for roadbed is laid. The saline-alkali soil-based polymer cement is added to the original saline-alkali soil in a ratio of geopolymer cement: saline-alkali soil = 1:8, and water is sprayed to supplement the soil until the moisture content in the soil is 15%. The soil is vigorously stirred with a rotary tiller in a road mixing method, and after mixing well, it is rolled with a roller to form a road subgrade. The compaction degree of the saline-alkali soil solidified in the subgrade is 96%. After the construction of the last layer of the subgrade is completed, it is covered with a plastic film for water conservation maintenance. After the maintenance period of 7 days, the core is taken. The core sample is intact, the unconfined compressive strength of the core sample is 5 MPa (7d), and the softening coefficient is 0.9. After the freeze-thaw process in winter and spring, the road subgrade is intact without slurry boiling. Under strong sunlight, the strength does not decrease.

[0074] Comparative Example 1

[0075] The geopolymer cement of this comparative example is different from that of Example 1 in that its raw materials are only composed of slag powder and alkaline activator, and do not contain saline-alkali soil. 2 The mass of the slag powder is 6% of the mass of the slag powder.

[0076] The preparation process of the geopolymer cement in this comparative example is as follows: the slag powder and the alkaline activator are dried, crushed and vigorously stirred, the mixer speed is 45 rpm, and the stirring time is 10 minutes, so as to obtain the geopolymer cement in this comparative example. The unconfined compressive strength of the net slurry hardened body of the geopolymer cement at a water-cement ratio of 0.5 is 30 MPa at 3d, 60 MPa at 7d, 75 MPa at 28d, and the softening coefficient is 0.9.

[0077] The geopolymer cement obtained in this comparative example is applied to road subgrade construction. The first layer of saline-alkali soil for roadbed is laid on the compacted saline-alkali soil roadbed. The geopolymer cement is added to the original saline-alkali soil in a ratio of geopolymer cement: saline-alkali soil = 1:8, and water is sprayed to supplement the soil until the moisture content in the soil is 15%. The soil is vigorously stirred with a rotary tiller in a road mixing method. After mixing well, the soil is rolled with a roller to form a road subgrade. The compaction degree of the saline-alkali soil solidified in the subgrade is 96%. After the construction of the last layer of the subgrade is completed, it is covered with a plastic film for water-retaining maintenance. After the maintenance period of 7 days, the core is taken. The core sample has many cracks and falls apart at the touch. The unconfined compressive strength of the core sample cannot be measured. After the freeze-thaw process in winter and spring, a large number of cracks appear on the road subgrade, and there is no strength.

[0078] Comparative Example 2

[0079] The geopolymer cement of this comparative example is different from that of Example 1 in that its raw materials are only composed of saline-alkali soil and alkaline activator, wherein the alkaline activator (equivalent to Na 2 The mass of the saline-alkali soil is 6%.

[0080] The preparation process of the geopolymer cement in this comparative example is as follows: the saline-alkali soil and the alkaline activator are dried and ball-milled and then vigorously stirred at a mixer speed of 45 rpm and a stirring time of 10 minutes to obtain the geopolymer cement in this comparative example. The unconfined compressive strength of the net slurry hardened body of the geopolymer cement at a water-cement ratio of 0.5 is 0.7 MPa at 3d, 1.6 MPa at 7d, 2.7 MPa at 28d, and the softening coefficient is 0.5.

[0081] The geopolymer cement obtained in this comparative example is applied to the construction of road subgrade. On the rolled and compacted saline-alkali soil roadbed, the first layer of saline-alkali soil for roadbed is laid. The geopolymer cement is added to the original saline-alkali soil in a ratio of geopolymer cement: saline-alkali soil = 1:8, and water is sprayed to supplement the soil until the moisture content in the soil is 15%. The soil is vigorously stirred with a rotary tiller in the road mixing method, and after mixing well, it is rolled with a roller to form a road subgrade. The compaction degree of the saline-alkali soil solidified in the subgrade is 96%. After the construction of the last layer of the subgrade is completed, it is covered with a plastic film for water-retaining maintenance. After the maintenance period of 7 days, the core is taken. The core sample is intact, the unconfined compressive strength of the core sample is 1.5 MPa (7d), and the softening coefficient is 0.7. After the freeze-thaw process in winter and spring, a large number of cracks appear in the road subgrade, and there is no strength.

[0082] Comparative Example 3

[0083] The geopolymer cement of this comparative example is different from that of Example 1. The saline-alkali content of the saline-alkali soil used in this comparative example is converted into alkali metal oxide K 2 O+Na 2 O accounts for 2% by mass in saline-alkali soil.

[0084] The preparation process of the geopolymer cement in this comparative example is the same as that in Example 1. The unconfined compressive strength of the hardened pure paste of the geopolymer cement at a water-cement ratio of 0.5 is 10 MPa at 3d, 15 MPa at 7d, 20 MPa at 28d, and the softening coefficient is 0.8.

[0085] The geopolymer cement obtained in this comparative example is applied to road subgrade construction, and the construction process is the same as that in Example 1. After the last layer of the subgrade is constructed, it is covered with a plastic film and water-retaining maintenance is carried out. After curing for 7 days, the core is taken, and the core sample is intact. The unconfined compressive strength of the core sample is 1.5 MPa (7d), and the softening coefficient is 0.65. After the freeze-thaw process in winter and spring, freeze-thaw damage occurs in the road subgrade.

[0086] Comparative Example 4

[0087] The geopolymer cement of this comparative example is different from that of Example 1 in that the mass proportions of saline-alkali soil and slag powder in this comparative example are 20% and 80% respectively.

[0088] The preparation process of the geopolymer cement in this comparative example is the same as that in Example 1. The unconfined compressive strength of the hardened pure paste of the geopolymer cement at a water-cement ratio of 0.5 is 25 MPa at 3d, 35 MPa at 7d, 60 MPa at 28d, and the softening coefficient is 0.9.

[0089] The geopolymer cement obtained in this comparative example is applied to road subgrade construction, and the construction process is the same as that in Example 1. After the last layer of the subgrade is constructed, it is covered with a plastic film and water-retaining maintenance is carried out. After curing for 7 days, the core is taken, and the core sample is intact. The unconfined compressive strength of the core sample is 2.5 MPa (7d), and the softening coefficient is 0.5. After the freeze-thaw process in winter and spring, the road subgrade is damaged by the freeze-thaw process.

[0090] Comparative Example 5

[0091] The geopolymer cement of this comparative example is different from that of Example 1. In this comparative example, the mass proportions of saline-alkali soil and slag powder are 60% and 40% respectively.

[0092] The preparation process of the geopolymer cement in this comparative example is the same as that in Example 1. The unconfined compressive strength of the hardened pure paste of the geopolymer cement at a water-cement ratio of 0.5 is 5 MPa at 3d, 15 MPa at 7d, 25 MPa at 28d, and the softening coefficient is 0.85.

[0093] The geopolymer cement obtained in this comparative example is applied to road subgrade construction, and the construction process is the same as that in Example 1. After the last layer of the subgrade is constructed, it is covered with a plastic film and water-retaining maintenance is carried out. After curing for 7 days, the core is taken, and the core sample is intact. The unconfined compressive strength of the core sample is 1.5 MPa (7d), and the softening coefficient is 0.5. After the freeze-thaw process in winter and spring, although a small amount of cracks appear in the road subgrade, the road condition is basically intact.

[0094] Example 2

[0095] The geopolymer cement of this embodiment is different from that of Example 1. The saline-alkali content of the saline-alkali soil used in this comparative example is converted into alkali metal oxide K 2 O+Na 2 O accounts for 5% of the mass in saline-alkali soil

[0096] The preparation process of the geopolymer cement of this embodiment is the same as that of embodiment 1. The unconfined compressive strength of the hardened pure paste of the geopolymer cement at a water-cement ratio of 0.5 is 20 MPa at 3d, 30 MPa at 7d, 80 MPa at 28d, and the softening coefficient is 0.95.

[0097] The geopolymer cement obtained in this comparative example is applied to road subgrade construction, and the construction process is the same as that in Example 1. After the last layer of the subgrade is constructed, it is covered with a plastic film and water-retaining maintenance is carried out. After curing for 7 days, the core is taken, and the core sample is intact. The unconfined compressive strength of the core sample is 2.5 MPa (7d), and the softening coefficient is 0.8. After the freeze-thaw process in winter and spring, the road subgrade is intact.

[0098] Example 3

[0099] The raw materials of the single-component geopolymer cement of this embodiment are composed of saline-alkali soil, slag powder, straw ash, silica fume, and alkaline activator, wherein saline-alkali soil accounts for 35%, slag powder accounts for 35%, straw ash accounts for 25%, silica fume accounts for 5%, and alkaline activator (equivalent to Na 2 The mass of O) accounts for 5% of the sum of the mass of saline-alkali soil, slag powder, straw ash and silica fume.

[0100] Specifically, the saline-alkali soil used in this embodiment is the silty saline-alkali soil at the bottom of a drainage ditch in Bachu County, southern Xinjiang (its composition is the same as that in Example 1), and the particle size of the saline-alkali soil is less than 200 mesh; the slag powder is made by grinding water-quenched blast furnace slag, with a specific surface area of ​​400m 2 / kg, product grade S95; SiO 2 The content is 95%; the straw ash is the straw burning ash of the biomass power plant, the residual carbon content is 5%, and the moisture content is 0.9%; the alkaline activator is composed of sodium hydroxide and sodium silicate, the modulus of sodium silicate in the alkaline activator is 2, and the proportion of sodium silicate is 70%.

[0101] The preparation process of the single-component saline-alkali soil-based polymer cement of this embodiment includes:

[0102] 1) weighing saline-alkali soil and alkaline activator according to the mixing ratio, drying and ball milling to form super-alkaline saline-alkali soil powder, the drying temperature is 290° C., and the moisture content of the super-alkaline soil powder is less than 1%;

[0103] 2) Super alkaline saline-alkali soil powder, slag powder, straw ash and silica fume are weighed according to the mix ratio, and vigorously stirred in a high-power mixer at a mixer speed of 60 rpm for 5 minutes to obtain saline-alkali soil-based polymer cement. The saline-alkali soil-based polymer cement has a hardened body strength of 23 MPa at 3d, 37 MPa at 7d, 91 MPa at 28d at a water-cement ratio of 0.5, and a softening coefficient of 0.95.

[0104] The single-component saline-alkali soil-based polymer cement of this embodiment is used for the solidification treatment of saline-alkali soil, specifically comprising: adding the obtained saline-alkali soil-based polymer cement to the original saline-alkali soil in Bachu County in a ratio of cement: saline-alkali soil = 1:1.5, and adding water to the required water-cement ratio of 0.5, and vigorously stirring to obtain a curable saline-alkali soil slurry, injecting the slurry into a 70.7mm×70.7mm×70.7mm mortar test mold, and vibrating and forming it, and then curing it under the curing conditions of 20°C and relative humidity of 90% to 3 days, 7 days, and 28 days. The unconfined compressive strength at each age is 4MPa (3d); 7MPa (7d); 12MPa (28d), and the softening coefficient is 0.9. After 25 freeze-thaw cycles from room temperature to -20°C, the strength and mass losses are negligible.

[0105] The saline-alkali soil-based polymer cement obtained in this embodiment is applied to the construction of road subgrade. On the compacted saline-alkali soil roadbed, the first layer of saline-alkali soil for roadbed is laid. The saline-alkali soil-based polymer cement is added to the original saline-alkali soil in a ratio of geopolymer cement: saline-alkali soil = 1:10, and water is sprayed to supplement the soil until the moisture content in the soil is 15%. The soil is vigorously stirred with a rotary tiller in a road mixing method, and after mixing well, it is rolled with a roller to form a road subgrade. The compaction degree of the saline-alkali soil solidified in the subgrade is 94%. After the construction of the last layer of the subgrade is completed, it is covered with a plastic film for water conservation maintenance. After the maintenance period of 7 days, the core is taken. The core sample is intact, the unconfined compressive strength of the core sample is 3.5 MPa (7d), and the softening coefficient is 0.9. After the freeze-thaw process in winter and spring, the road subgrade is intact without slurry boiling. Under strong sunlight, the strength does not decrease.

[0106] Example 4

[0107] The single-component saline-alkali soil-based polymer cement of this embodiment is composed of saline-alkali soil, straw ash, silica fume, and alkaline activator, wherein the saline-alkali soil accounts for 40%, the straw ash accounts for 55%, the silica fume accounts for 5%, and the alkaline activator (equivalent to Na 2 The mass of O) accounts for 6% of the sum of the mass of saline-alkali soil, straw ash and silica ash.

[0108] Specifically, the saline-alkali soil in this embodiment is silty saline-alkali soil (with the same composition as in Example 1) from a drainage ditch in Bachu County, southern Xinjiang, and the particle size of the saline-alkali soil is less than 200 mesh; SiO 2The content is 98%; the straw ash is the straw burning ash of the biomass power plant, with a residual carbon content of 3% and a moisture content of 0.5%; the alkaline activator is composed of sodium hydroxide and sodium silicate, and the modulus of the sodium silicate in the alkaline activator is 2, and the sodium silicate accounts for 50%.

[0109] The preparation process of the single-component saline-alkali soil-based polymer cement of this embodiment is as follows:

[0110] 1) weighing saline-alkali soil and alkaline activator according to the mixing ratio, drying and ball milling to form super alkaline soil powder, the drying temperature is 250° C., and the moisture content of the super alkaline soil powder is less than 1%;

[0111] 2) Super alkaline soil powder, straw ash and silica fume are weighed according to the mix ratio, and vigorously stirred in a high-powered mixer at a speed of 45 rpm for 10 minutes to obtain saline-alkali soil-based polycement. The net slurry hardening strength of the saline-alkali soil-based polycement at a water-cement ratio of 0.5 is 15 MPa at 3d, 28 MPa at 7d, 35 MPa at 28d, and the softening coefficient is 0.9.

[0112] The single-component saline-alkali soil-based polycement of this embodiment is applied as follows:

[0113] 1) The saline-alkali soil-based polycement obtained in this embodiment is added to the original saline-alkali soil in a ratio of cement: soil = 1:9, and water is added to the required water-cement ratio, the water-cement ratio is 0.4, and vigorously stirred to obtain a curable saline-alkali soil slurry, which is injected into a 70.7 mm × 70.7 mm × 70.7 mm mortar test mold and vibrated to form, and then cured at 20 ° C and 90% relative humidity. Conditions to 3 days, 7 days, and 28 days of age, the unconfined compressive strength of each age is 0.5 MPa (3d); 1.7 MPa (7d); 3 MPa (28d), the softening coefficient is 0.85, and the number of freeze-thaw cycles from room temperature to -20 ° C is 25 times, and the strength and mass loss are negligible.

[0114] 2) Ditch slope construction

[0115] The saline-alkali soil-based polymer cement obtained in this example is added in a ratio of cement: saline-alkali soil = 1:9. Figure 3The original saline-alkali soil at the bottom of the drainage channel 1 shown in the figure is supplemented with saline-alkali water 2 to a water-cement ratio of 0.6, and vigorously stirred to obtain a solidified saline-alkali soil slurry, which is poured into the slope casting area surrounded by the template support for the drainage channel slope protection construction, and vibrated to form. Before the final setting, the template is removed, and a plurality of parallel holes are orderly inserted in the horizontal direction of the slope into the unconstructed saline-alkali soil body 5, that is, a hole channel (i.e., the saline-alkali water discharge channel 3) is formed every 100mm up and down. The saline-alkali components formed in the adjacent cultivated land are smoothly discharged to the alkali drainage channel through this channel along with the seepage water. After the slope hardens, the template is removed and covered with plastic film for water conservation maintenance. After curing for 7 days, the core is taken and the core sample is intact. The 7d unconfined compressive strength of the core sample is 1.5MPa (7d), and the softening coefficient is 0.85. After the freeze-thaw process in winter and spring, the slope is intact. Under strong sunlight, the strength does not decrease. The seepage drainage channel on the alkali drainage channel solidified soil slope 4 obtained by construction will not be blocked for a long time.

[0116] 3) Roadbed

[0117] The saline-alkali soil-based polymer cement obtained in this embodiment is applied to the construction of road subgrade. On the compacted saline-alkali soil roadbed, the first layer of saline-alkali soil for roadbed is laid. The saline-alkali soil-based polymer cement is added to the original saline-alkali soil in a ratio of geopolymer cement: saline-alkali soil = 1:12, and water is sprayed to supplement the soil until the moisture content in the soil is 15%. The soil is vigorously stirred with a rotary tiller in a road mixing method, and after mixing well, it is rolled with a roller to form a road subgrade. The compaction degree of the saline-alkali soil solidified in the subgrade is 97%. After the construction of the last layer of the subgrade is completed, it is covered with a plastic film for water conservation maintenance. After the maintenance period of 7 days, the core is taken. The core sample is intact, the unconfined compressive strength of the core sample is 2 MPa (7d), and the softening coefficient is 0.85. After the freeze-thaw process in winter and spring, the road subgrade is intact without slurry boiling. Under strong sunlight, the strength does not decrease.

[0118] Example 5

[0119] The single-component geopolymer cement of this embodiment is composed of saline-alkali soil, slag powder, straw ash, and alkaline activator, wherein saline-alkali soil accounts for 50%, slag powder accounts for 25%, straw ash accounts for 25%, and alkaline activator (equivalent to Na 2 The mass of the raw materials is 3% of the total mass of saline-alkali soil, slag powder and straw ash.

[0120] Specifically, the saline-alkali soil in this embodiment is silty saline-alkali soil from a drainage canal in Bachu County, southern Xinjiang (its composition is the same as in Example 1), and the particle size of the saline-alkali soil is less than 200 mesh; the slag powder is made by grinding water-quenched blast furnace slag, with a specific surface area of ​​600m 2 / kg, the product grade is S105; the straw ash is the straw burning ash from the biomass power plant, with a residual carbon content of 3% and a moisture content of 0.5%; the alkaline activator is composed of sodium hydroxide and sodium silicate, and the modulus of sodium silicate in the alkaline activator is 1, and the mass of sodium silicate accounts for 70%.

[0121] The preparation process of the single-component saline-alkali soil-based polymer cement of this embodiment is as follows:

[0122] 1) weighing saline-alkali soil and alkaline activator according to the mixing ratio, drying and ball milling to form super-alkaline saline-alkali soil powder, the drying temperature is 250° C., and the moisture content of the super-alkaline soil powder is 0.5%;

[0123] 2) Super alkaline soil powder and slag powder are weighed according to the mix ratio, and vigorously stirred in a high-power mixer at a mixer speed of 48 rpm for 8 minutes to obtain saline-alkali soil-based polymer cement. The saline-alkali soil-based polymer cement has a hardened body strength of 20 MPa at 3d, 30 MPa at 7d, 60 MPa at 28d at a water-cement ratio of 0.5, and a softening coefficient of 0.95.

[0124] The single-component saline-alkali soil-based polycement of this embodiment is applied as follows:

[0125] 1) The saline-alkali soil-based polycement obtained in this embodiment is added to the original saline-alkali soil in a ratio of cement: soil = 1:4, and water is added to the required water-cement ratio, the water-cement ratio is 0.5, and vigorously stirred to obtain a curable saline-alkali soil slurry, which is injected into a 70.7 mm × 70.7 mm × 70.7 mm mortar test mold and vibrated to form, and then cured at 20 ° C and relative humidity 90% to 3 days, 7 days, and 28 days. The unconfined compressive strength at each age is 0.9 MPa (3d); 2.5 MPa (7d); 4.5 MPa (28d), the softening coefficient is 0.9, and the strength and mass loss are negligible after 25 freeze-thaw cycles from room temperature to -20 ° C.

[0126] 2) Ditch slope construction

[0127] The saline-alkali soil-based polymer cement obtained in this example is added in a ratio of cement: saline-alkali soil = 1:4. Figure 3The original saline-alkali soil at the bottom of the drainage channel 1 shown in the figure is supplemented with saline-alkali water 2 to a water-cement ratio of 0.4, and vigorously stirred to obtain a solidified saline-alkali soil slurry, which is poured into the slope casting area surrounded by the template support for the drainage channel slope protection construction, and vibrated to form. Before the final setting, the template is removed, and a plurality of parallel holes are orderly inserted in the horizontal direction of the slope into the unconstructed saline-alkali soil body 5, that is, a hole channel (i.e., the saline-alkali water discharge channel 3) is formed every 80mm up and down, so that The saline-alkali components formed in the adjacent cultivated land are smoothly discharged to the alkali drainage channel through this channel along with the seepage water. After the slope hardens, the template is removed and covered with plastic film for water conservation maintenance. The core is taken after 7 days of maintenance. The core sample is intact. The 7d unconfined compressive strength of the core sample is 3.5MPa (7d), and the softening coefficient is 0.9. After the freeze-thaw process in winter and spring, the slope is intact. Under strong sunlight, the strength does not decrease. The seepage drainage channel on the alkali drainage channel solidified soil slope 4 obtained by construction will not be blocked for a long time.

[0128] 3) Roadbed

[0129] The saline-alkali soil-based polymer cement obtained in this embodiment is applied to the construction of road subgrade. On the compacted saline-alkali soil roadbed, the first layer of saline-alkali soil for roadbed is laid. The saline-alkali soil-based polymer cement is added to the original saline-alkali soil in a ratio of geopolymer cement: saline-alkali soil = 1:9, and water is sprayed to supplement the soil until the moisture content in the soil is 15%. The soil is vigorously stirred with a rotary tiller in a road mixing method, and after mixing well, it is rolled with a roller to form a road subgrade. The compaction degree of the saline-alkali soil solidified in the subgrade is 95%. After the construction of the last layer of the subgrade is completed, it is covered with a plastic film for water conservation maintenance. After the maintenance period of 7 days, the core is taken. The core sample is intact, the unconfined compressive strength of the core sample is 3 MPa (7d), and the softening coefficient is 0.85. After the freeze-thaw process in winter and spring, the road subgrade is intact without slurry boiling. Under strong sunlight, the strength does not decrease.

[0130] Example 6

[0131] The raw materials of the single-component geopolymer cement of this embodiment are composed of saline-alkali soil, slag powder, silica fume, and alkaline activator, wherein saline-alkali soil accounts for 50%, slag powder accounts for 45%, silica fume accounts for 5%, and alkaline activator (equivalent to Na 2 O) accounts for 6% of the sum of the mass of saline-alkali soil, slag powder and silica fume;

[0132] Specifically, the saline-alkali soil in this embodiment is silty saline-alkali soil from a drainage canal in Bachu County, southern Xinjiang (its composition is the same as in Example 1), and the particle size of the saline-alkali soil is less than 200 mesh; the slag powder is made by grinding water-quenched blast furnace slag, with a specific surface area of ​​600m 2 / kg, product grade is S105; SiO in silica ash 2Content 98%; the alkaline activator is composed of sodium hydroxide and sodium silicate. The modulus of sodium silicate in the alkaline activator is 2, and the proportion of sodium silicate is 65%.

[0133] The preparation process of the single-component saline-alkali soil-based polymer cement of this embodiment is as follows:

[0134] 1) weighing saline-alkali soil and alkaline activator according to the mixing ratio, drying and ball milling to form super alkaline soil powder, the drying temperature is 250° C., and the moisture content of the super alkaline soil powder is 0.5%;

[0135] 2) Super alkaline soil powder, slag powder and silica fume are weighed according to the mix ratio, and vigorously stirred in a high-power mixer at a speed of 60 rpm for 9 minutes to obtain saline-alkali soil-based polymer cement. The saline-alkali soil-based polymer cement has a hardened body strength of 20 MPa at 3d, 38 MPa at 7d, 87 MPa at 28d at a water-cement ratio of 0.5, and a softening coefficient of 0.95.

[0136] The single-component saline-alkali soil-based polycement of this embodiment is applied as follows:

[0137] 1) The saline-alkali soil-based polycement obtained in this embodiment is added to the original saline-alkali soil in a ratio of cement: soil = 1:6, and water is added to the required water-cement ratio, the water-cement ratio is 0.5, and vigorously stirred to obtain a curable saline-alkali soil slurry, and the slurry is injected into a 70.7 mm × 70.7 mm × 70.7 mm mortar test mold, and vibrated to form, and then cured at 20 ° C and relative humidity 90% to 3 days, 7 days, and 28 days. The unconfined compressive strength at each age is 0.8 MPa (3d); 1.98 MPa (7d); 4.5 MPa (28d), the softening coefficient is 0.85, and the strength and mass loss are negligible after 25 freeze-thaw cycles from room temperature to -20 ° C.

[0138] 2) Ditch slope construction

[0139] The saline-alkali soil-based polymer cement obtained in this example is added in a ratio of cement: saline-alkali soil = 1:6. Figure 3The original saline-alkali soil at the bottom of the drainage channel 1 shown in the figure is supplemented with saline-alkali water 2 until the water-cement ratio is 0.35, and then vigorously stirred to obtain a solidified saline-alkali soil slurry. The slurry is poured into the slope casting area surrounded by the template support for the drainage channel slope protection construction, and vibrated to form. Before the final setting, the template is removed, and multiple parallel holes are orderly inserted in the horizontal direction of the slope into the unconstructed saline-alkali soil body 5, that is, a hole channel (i.e., saline-alkali water discharge channel 3) is formed every 90 mm up and down. The saline-alkali components formed in the adjacent cultivated land are smoothly discharged to the alkali drainage channel through the channel along with the seepage and drainage. After the slope hardens, the template is removed and covered with plastic film for water conservation maintenance. The core is taken after 7 days of maintenance. The core sample is complete. The 7d unconfined compressive strength of the core sample is 3.5MPa (7d), and the softening coefficient is 0.9. After the freeze-thaw process in winter and spring, the slope is intact. Under strong sunlight, the strength does not decrease. The seepage and drainage channel on the alkali drainage channel solidified soil slope 4 obtained by construction will not be blocked for a long time.

[0140] 3) Roadbed

[0141] The saline-alkali soil-based polymer cement obtained in this embodiment is applied to the construction of road subgrade. On the compacted saline-alkali soil roadbed, the first layer of saline-alkali soil for roadbed is laid. The saline-alkali soil-based polymer cement is added to the original saline-alkali soil in a ratio of geopolymer cement: saline-alkali soil = 1:10, and water is sprayed to supplement the soil until the moisture content in the soil is 13%. The soil is vigorously stirred with a rotary tiller in a road mixing method, and after mixing well, it is rolled with a roller to form a road subgrade. The compaction degree of the saline-alkali soil solidified in the subgrade is 95%. After the construction of the last layer of the subgrade is completed, it is covered with a plastic film for water conservation maintenance. After the maintenance period is 7 days, the core is taken, and the core sample is intact. The unconfined compressive strength of the core sample is 3.5 MPa (7d), and the softening coefficient is 0.85. After the freeze-thaw process in winter and spring, the road subgrade is intact without slurry boiling. Under strong sunlight, the strength does not decrease.

[0142] Example 7

[0143] The raw material composition of the single-component geopolymer cement of this embodiment is basically the same as that of Embodiment 5, with the main difference being that the alkaline activator in this embodiment adopts powdered raw materials, and the alkaline activator is composed of sodium hydroxide, sodium silicate and sodium carbonate, wherein the modulus of sodium silicate is 2, sodium silicate accounts for 65%, sodium hydroxide accounts for 20%, and sodium carbonate accounts for 15%.

[0144] The preparation process of the single-component saline-alkali soil-based polymer cement of this embodiment is as follows:

[0145] Weigh the dried raw materials according to the mass mix ratio, and stir them vigorously in a high-power mixer at a speed of 65 rpm for 5 minutes to obtain saline-alkali soil-based polymer cement. The saline-alkali soil-based polymer cement has a hardened body strength of 22 MPa at 3d, 35 MPa at 7d, and 85 MPa at 28d when the water-cement ratio is 0.5, and the softening coefficient is ≥0.9.

[0146] The single-component saline-alkali soil-based polycement of this embodiment is applied as follows:

[0147] 1) The saline-alkali soil-based polycement obtained in this embodiment is added to the original saline-alkali soil in a ratio of cement: soil = 1:6, and water is added to the required water-cement ratio, the water-cement ratio is 0.5, and vigorously stirred to obtain a curable saline-alkali soil slurry, and the slurry is injected into a 70.7 mm × 70.7 mm × 70.7 mm mortar test mold, and vibrated to form, and then cured at 20 ° C and relative humidity 90% to 3 days, 7 days, and 28 days. The unconfined compressive strength at each age is 0.5 MPa (3d); 1.5 MPa (7d); 4.1 MPa (28d), the softening coefficient is 0.85, and the strength and mass loss are negligible after 25 freeze-thaw cycles from room temperature to -20 ° C.

[0148] 2) Ditch slope construction

[0149] The saline-alkali soil-based polymer cement obtained in this example is added in a ratio of cement: saline-alkali soil = 1:6. Figure 3 The original saline-alkali soil at the bottom of the drainage channel 1 shown in the figure is supplemented with saline-alkali water 2 until the water-cement ratio is 0.35, and then vigorously stirred to obtain a solidified saline-alkali soil slurry. The slurry is poured into the slope casting area surrounded by the template support for the drainage channel slope protection construction, and vibrated to form. Before the final setting, the template is removed, and multiple parallel holes are orderly inserted in the horizontal direction of the slope into the unconstructed saline-alkali soil body 5, that is, a hole channel (i.e., saline-alkali water discharge channel 3) is formed every 90 mm up and down. The saline-alkali components formed in the adjacent cultivated land are smoothly discharged to the alkali drainage channel through the channel along with the seepage and drainage. After the slope hardens, the template is removed and covered with plastic film for water conservation maintenance. The core is taken after 7 days of maintenance. The core sample is complete. The 7d unconfined compressive strength of the core sample is 2.5MPa (7d), and the softening coefficient is 0.8. After the freeze-thaw process in winter and spring, the slope is intact. Under strong sunlight, the strength does not decrease. The seepage and drainage channel on the alkali drainage channel solidified soil slope 4 obtained by construction will not be blocked for a long time.

[0150] 3) Roadbed

[0151] The saline-alkali soil-based polymer cement obtained in this embodiment is applied to the construction of road subgrade. On the compacted saline-alkali soil roadbed, the first layer of saline-alkali soil for roadbed is laid. The saline-alkali soil-based polymer cement is added to the original saline-alkali soil in a ratio of geopolymer cement: saline-alkali soil = 1:10, and water is sprayed to supplement the soil until the moisture content in the soil is 12%. The soil is vigorously stirred with a rotary tiller in a road mixing method, and after mixing well, it is rolled with a roller to form a road subgrade. The compaction degree of the saline-alkali soil solidified in the subgrade is 95%. After the construction of the last layer of the subgrade is completed, it is covered with a plastic film and water-retaining maintenance is carried out. After the maintenance period is 7 days, the core is taken, and the core sample is intact. The unconfined compressive strength of the core sample is 2.9 MPa (7d), and the softening coefficient is 0.85. After the freeze-thaw process in winter and spring, the road subgrade is intact without slurry boiling. Under strong sunlight, the strength does not decrease.

[0152] Example 8

[0153] The raw materials of the single-component geopolymer cement of this embodiment are composed of saline-alkali soil, slag powder, silica fume, straw ash, and alkaline activator, wherein saline-alkali soil accounts for 40%, slag powder accounts for 45%, silica fume accounts for 5%, straw ash accounts for 10%, and alkaline activator (equivalent to Na 2 The mass of the raw materials is 6% of the total mass of saline-alkali soil, slag powder, silica fume and straw ash.

[0154] The saline-alkali soil used in this embodiment is the silty saline-alkali soil from a drainage canal in Bachu County, southern Xinjiang, and the particle size of the saline-alkali soil is less than 200 mesh; the mineral powder is made by grinding water-quenched blast furnace slag with a specific surface area of ​​600m 2 / kg, product grade is S105; SiO in silica ash 2 The content is 98%; the straw ash is the straw burning ash of the biomass power plant, with a residual carbon content of 3% and a moisture content of 0.5%; the alkaline activator is composed of sodium hydroxide, sodium silicate, sodium carbonate, and sodium sulfate, and each component in the alkaline activator is a powder, the sodium silicate is a quick-soluble sodium silicate powder with a modulus of 2, and the sodium silicate accounts for 65%.

[0155] The preparation process of the single-component saline-alkali soil-based polymer cement of this embodiment is as follows:

[0156] Using powder activator raw materials, dried saline-alkali soil powder, slag powder, straw ash, silica fume and powdered alkaline activator are weighed according to the mix ratio, and vigorously stirred in a high-power mixer at a mixer speed of 50 rpm and a stirring time of 10 minutes to obtain saline-alkali soil-based polymer cement. The saline-alkali soil polymer cement has a net paste hardening strength of 20 MPa at 3d, 40 MPa at 7d and 95 MPa at 28d when the water-cement ratio is 0.5, and a softening coefficient ≥0.9.

[0157] The single-component saline-alkali soil-based polymer cement of this embodiment is used for the solidification treatment of saline-alkali soil, specifically including: adding the saline-alkali soil-based polymer cement obtained in this embodiment to the original saline-alkali soil of a drainage ditch in Bachu County according to the ratio of cement: soil = 1:2, and adding water to the required water-cement ratio, the water-cement ratio is 0.6, and vigorously stirring to obtain a curable saline-alkali soil slurry, injecting the slurry into a 70.7mm×70.7mm×70.7mm mortar test mold, and vibrating and forming, and then curing to 3 days, 7 days, and 28 days under the curing conditions of 20°C and relative humidity of 90%. The unconfined compressive strength of each age is 3.5MPa (3d); 6MPa (7d); 12MPa (28d), the softening coefficient is 0.9, and the strength and mass loss are negligible after 25 freeze-thaw cycles from room temperature to -20°C.

[0158] Comparative Example 6

[0159] The geopolymer cement of this comparative example is different from that of Example 8. The raw materials of the cement of this comparative example do not contain saline-alkali soil. The raw materials are composed of slag powder, silica fume, straw ash, and alkaline activator, wherein the slag powder accounts for 75%, the silica fume accounts for 8.3%, the straw ash accounts for 16.7%, and the alkaline activator (equivalent to Na 2 The mass proportion of the slag powder, silica fume and straw ash is 6% of the total mass of the slag powder, silica fume and straw ash.

[0160] The preparation process of the geopolymer cement of this comparative example is:

[0161] Using powder activator raw materials, dried slag powder, straw ash, silica fume and powdered alkaline activator are weighed according to the mix ratio, and vigorously stirred in a high-power mixer at a mixer speed of 50 rpm and a stirring time of 10 minutes to obtain geopolymer cement. The net paste hardened body strength of the geopolymer cement at a water-cement ratio of 0.5 is 30 MPa at 3d, 65 MPa at 7d, 75 MPa at 28d, and the softening coefficient is 0.85.

[0162] The geopolymer cement of this comparative example is used for the solidification treatment of saline-alkali soil, specifically comprising: adding the geopolymer cement of this comparative example to the original saline-alkali soil of a drainage ditch in Bachu County in a ratio of cement: soil = 1:2, and adding water to the required water-cement ratio, the water-cement ratio is 0.6, and vigorously stirring to obtain a solidifiable saline-alkali soil slurry, injecting the slurry into a 70.7mm×70.7mm×70.7mm mortar test mold, and vibrating and forming, and then curing to 3 days, 7 days, and 28 days under the curing conditions of 20°C and relative humidity of 90%. The unconfined compressive strength at each age is 2.5MPa (3d); 5MPa (7d); 7.5MPa (28d), the softening coefficient is 0.75, and after 25 freeze-thaw cycles from room temperature to -20°C, the strength and quality loss are obvious.

Claims

1. A saline-alkali soil-based polymer cement, characterized in that: The raw materials include crystalline silicon-aluminum raw materials and amorphous silicon-aluminum raw materials, wherein the mass of the crystalline silicon-aluminum raw materials accounts for 35% to 50% of the total amount of crystalline and amorphous silicon-aluminum raw materials, and the content of silicon aluminum oxide in the crystalline silicon-aluminum raw materials is not less than 65% of the total amount of the crystalline silicon-aluminum raw materials.

2. The saline-alkali soil-based polymer cement according to claim 1, characterized in that: The compressive strength of the hardened pure paste of the saline-alkali soil-based polymer cement at a water-cement ratio of 0.5 is 15-25 MPa at 3 days, 25-35 MPa at 7 days, 35-95 MPa at 28 days, and the softening coefficient is ≥0.9; And / or the crystalline silicon-alumina raw material is saline-alkali soil, and the amorphous silicon-alumina raw material is silicon-alumina industrial solid waste.

3. The saline-alkali soil-based polymer cement according to claim 2, characterized in that: The salt-alkali content of the saline-alkali soil converted into alkali metal oxides is not less than 5%; And / or the raw material of the geopolymer cement further comprises an additional alkaline activator, the mass of the additional alkaline activator is 3% to 6% of the total amount of saline-alkali soil and silicon-alumina industrial solid waste.

4. The saline-alkali soil-based polymer cement according to claim 3, characterized in that: The silicon-aluminium industrial solid waste is one of slag powder, straw ash, silica ash or any combination thereof; and / or The added alkaline activator comprises at least two of alkali metal hydroxides, silicates, sulfates and carbonates; or the added alkaline activator is a combination of sodium silicate and at least one of alkali metal hydroxides, sulfates and carbonates, and the mass of sodium silicate accounts for 50% to 80% of the total amount of the added alkaline activator, and the modulus of sodium silicate ranges from 1 to 2.

5. A method for preparing saline-alkali soil-based polymer cement according to any one of claims 1 to 4, characterized in that: include: The step of uniformly mixing raw materials including crystalline silicon-aluminum raw materials, amorphous silicon-aluminum raw materials and an external alkaline activator.

6. A solidifiable saline-alkali soil slurry, characterized in that: The raw materials include original saline-alkali soil and the saline-alkali soil-based polymer cement described in any one of claims 1 to 4 or prepared in claim 5.

7. The curable saline-alkali soil slurry according to claim 6, characterized in that: The mass ratio of the saline-alkali soil-based polymer cement to the original saline-alkali soil is 1:1.5-1:9, 1:2-1:10 or 1:8-1:12; and / or the water-cement ratio of the solidifiable saline-alkali soil slurry is 0.35 to 1.0, preferably 0.35 to 0.6; and / or the slurry has an unconfined compressive strength of 0.5-4 MPa, 1.5-7 MPa, 3-12 MPa, respectively, at 3 days, 7 days, and 28 days of curing under curing conditions of 20° C. and a relative humidity of 90%, and a softening coefficient of ≥0.85; And / or the unconfined compressive strength of the slurry after solidification and water-retaining curing for 7 days is 1 to 5 MPa, and the softening coefficient is ≥0.

85.

8. A method for preparing a curable saline-alkali soil slurry according to claim 6 or 7, characterized in that: include: The original saline-alkali soil is mixed with the saline-alkali soil-based polymer cement, and water is added to reach a required water-cement ratio.

9. A saline-alkali stabilized soil, characterized in that: The raw material of the saline-alkali solidified soil comprises the saline-alkali soil-based polymer cement described in any one of claims 1 to 4, or prepared in claim 5, or the saline-alkali solidified soil is formed by solidifying the curable saline-alkali soil slurry described in claim 6 or 7, or prepared in claim 8.

10. Use of the saline-alkali soil-based polymer cement as described in any one of claims 1 to 4 or prepared in claim 5, or the solidifiable saline-alkali soil slurry as described in claim 6 or 7 or prepared in claim 8, or the saline-alkali solidified soil as described in claim 9 in soil solidification, ditch slope or road subgrade.

Citation Information

Patent Citations

  • A single-component alkali-activated cementitious material using lime-sodium carbonate as an activator

    CN108218264B

  • Fly ash, blaster furnace slag and water-rich carbide slag matrix geopolymer and preparation method thereof

    CN110776279A

  • Single-component geopolymer curing agent based on multi-element solid waste and preparation method of single-component geopolymer curing agent

    CN113354310A

  • Composite foundation of single-component geopolymer reinforced soil body and construction method of composite foundation

    CN114960610A